Phosphorus doses alter the ionic homeostasis of cowpea irrigated with saline water - Francisco V. da S. Sá; Ivan E. da Silva; Miguel Ferreira Neto; Yuri B. de Lima; Emanoela P. de Paiva; Hans R. Gheyi (Revista Brasileira de Engenharia Agrícola e Ambiental)
HIGHLIGHTS Irrigation using water with electrical conductivity above 2.5 dS m-1 is not adequate for ‘Paulistinha’ cowpea. Increment in phosphorus dose does not increase phosphorus content in cowpea plant. Under salt stress conditions, cowpea plants require lower doses of phosphorus.